Comment on "A Tag Encoding Scheme Against Pollution Attack to Linear Network Coding" - Chang, Jinyong; Shao, Bilin; Ji, Yanyan; Bian, Genqing (IEEE transactions on parallel and distributed systems, 2020)
In 2014, Wu et al. proposed a tag encoding scheme, named KEPTE, to protect network coding against pollution attack. They also carefully analyzed the security of KEPTE based on the transmission of a data file through their key-pre-distributed network. In this article, we point out that their security analysis only holds for single data file transmitted in this network. If multiple files are multicasted though it, then any adversary may completely recover source node's signing key. A concrete example says that, after pre-distributing 90 keys to all the nodes in the network, it only allows to securely transmit (at most) 3 data files. More importantly, this scheme is completely insecure in standard security model for network model since the adversary is allowed to make polynomial times queries on any data files of its choice before outputting its final forgery. Finally, we also propose a twisted KEPTE scheme that is secure against any eavesdropping adversary no matter how many data files it has queried.